BENTUK TRADISI WAKER MASYARAKAT ANUS KABUPATEN SARMI PROVINSI PAPUA: Analisis Wacana Penyambutan Tamu - Wondiwoy, Lusi Hana Faniel; Mawene, Aleda; Mantiri, Grace J.M. (Melanesia : Jurnal Ilmiah Kajian Bahasa dan Sastra, 2018)
This article aims to reveal the waker tradition in the Anus community of Sarmi Regency of Papua Province. This research on wakers is focused on welcoming ceremony. In this case, Waker as an object of study because of its almost disappearing existence due to the entry of foreign culture into the Anus tribe society such as lemon lemon that is now quite famous in Sarmi. After the entry of these cultures, the Anus people lack and maintain the waker that is one of their characteristics. In addition to the many waker singers who have died, appearing indifferent nature of some local people.The waker tradition was chosen as one of the oral traditions of the Anus community in Bonggo Barat District, Sarmi Regency became the object of discourse study in the form aspect. The focus of the study refers to the type of waker used in a welcome reception called tokour di. This research is deemed necessary to keep this tradition maintained and inherited by the local community. In addition, it plays an important role in the value of education for contributions to the curriculum of teaching Indonesian Language and Literature in poetry learning, as well as the realization of the preservation of oral literature.The results show that the waker text contains the sound of speech that often appears at the beginning of the line and at the end of the line on a particular stanza. Variations of sound are words, phrases, sentences, and particles. In addition, there is also alliteration and consonance. Fourth, Waker is a discourse formed by context. Therefore, in it there is the feldof discourse, the discourse of discourse, and the means of discourse. Discourse feld involves all existing and adapted speakers of waker text with events on tokour event at. Discourse explains about everything contained in tokour in the event. The means of discourse is the way of delivering the waker in oral form in tokour event.